Special Methods Of Using Oil Fields With High Viscosity (The Peerian Journal, 2023)
The coefficient of coverage can also decrease with formation seepage, because when the pressure gradient is less than the pressure gradient of the limit structure failure in the oil, the oil is less immobile in the low-permeability layers and mainly moves in the high-permeability layers. If the pressure gradients in the formation are smaller than the pressure gradient of the dynamic displacement of this oil, zones can be formed where the movement of oil with an almost intact structure is observed